The Effectiveness of Economic Learning During Covid-19 Pandemic (a Case Study of Economics Teacher of Senior High School in Klojen District of Malang City) - Adistya, Pragita Aci; Rokhmani, Lisa (International Education Trend Issues, 2024)
In Indonesia, the Covid-19 pandemic occurred due to the contagious and deadly corona virus. The government implements PSBB (Large-Scale Social Restrictions) and social distancing (maintaining distance). Learning activities at school turn into remote or online (online). In these circumstances, teachers use educational applications or platforms in carrying out learning activities, cell phones and laptops or computers as communication tools. Learning modules are given to students to learn independently. Learning effectiveness is carried out by achieving learning objectives by students.